Periodized versus non-periodized swimming training with equal total training load: Physiological, molecular and performance adaptations in Wistar rats - Lucas D. M. Forte; Natália A. Rodrigues; André V. Cordeiro; Thais de Fante; Laís A. P. Simino; Adriana S. Torsoni; Márcio A. Torsoni; Claudio A. Gobatto; Fúlvia B. Manchado-Gobatto; Clemens Fürnsinn (PLoS ONE, 2020)
This study investigated the effect of non-periodized training performed at 80, 100 and 120% of the anaerobic threshold intensity (AnT) and a linear periodized training model adapted for swimming rats on the gene expression of monocarboxylate transporters 1 and 4 (MCT1 and 4, in soleus and gastrocnemius muscles), protein contents, blood biomarkers, tissue glycogen, body mass, and aerobic and anaerobic capacities. Sixty Wistar rats were randomly divided into 6 groups (n = 10 per group): a baseline (BL; euthanized before training period), a control group (GC; not exercised during the training period), three groups exercised at intensities equivalent to 80, 100 and 120% of the AnT (G80, G100 and G120, respectively) at the equal workload and a linear periodized training group (GPE). Each training program lasted 12 weeks subdivided into three periods: basic mesocycle (6 weeks), specific mesocycle (5 weeks) and taper (1 week). Although G80, G100 and G120 groups were submitted to monotony workload (i.e. non-modulation at intensity or volume throughout the training program), rodents were evaluated during the same experimental timepoints as GPE to be able comparisons. Our main results showed that all training programs were capable to minimize the aerobic capacity decrease promoted by age, which were compared to control group. Rats trained in periodization model had reduced levels of lipid blood biomarkers and increased hepatic glycogen stores compared to all other trained groups. At the molecular level, only expressions of MCT1 in the muscle were modified by different training regimens, with MCT1 mRNA increasing in rats trained at lower intensities (G80), and MCT1 protein content showed higher values in non-periodized groups compared to pre-training and GPE. Here, training at different intensities but at same total workload promoted similar adaptations in rats. Nevertheless, our results suggested that periodized training seems to be optimize the physiological responses of rats.